2008
DOI: 10.1128/jb.00097-08
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Scaffoldin Gene, cipA , of Clostridium thermocellum with Impaired Cellulosome Formation and Cellulose Hydrolysis: Insertions of a New Transposable Element, IS 1447 , and Implications for Cellulase Synergism on Crystalline Cellulose

Abstract: Mutants of Clostridium thermocellum that had lost the ability to adhere to microcrystalline cellulose were isolated. Six of them that showed diminished ability to depolymerize crystalline cellulose were selected. Size exclusion chromatography of the proteins from the culture supernatant revealed the loss of the supramolecular enzyme complex, the cellulosome. However, denaturing sodium dodecyl sulfate-polyacrylamide gel electrophoresis resulted in extracellular protein patterns comparable to those of isolated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 33 publications
2
66
0
Order By: Relevance
“…In agreement with Zverlov et al, we have shown that cipA is essential for rapid solubilization of crystalline cellulose (13). However, contrary to what was reported previously, we observed that cipA deletion strains are able to solubilize Avicel microcrystalline cellulose (which is similar to the MN300 microcrystalline cellulose used by Zverlov et al).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In agreement with Zverlov et al, we have shown that cipA is essential for rapid solubilization of crystalline cellulose (13). However, contrary to what was reported previously, we observed that cipA deletion strains are able to solubilize Avicel microcrystalline cellulose (which is similar to the MN300 microcrystalline cellulose used by Zverlov et al).…”
Section: Discussionsupporting
confidence: 89%
“…Previous work has shown that the abilities to bind and to solubilize cellulose are linked (11,13). Thus, mutants deficient in cellulose binding are also deficient in cellulose solubilization.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In natural and recombinant systems, these synergistic effects are further augmented by an extra level of synergy resulting from the cellulosome's association with the surface of cells, yielding cellulose-enzyme-microbe (CEM) ternary complexes [89,[112][113][114][115][116][117][118]. CEM ternary complexes benefit from the effects of microbe-enzyme synergy, ultimately limiting the escape of hydrolysis products and enzymes, increasing access to substrate hydrolysis products, minimizing the distance products must diffuse before cellular uptake occurs, concentrating enzymes at the substrate surface, protecting hydrolytic enzymes from proteases and thermal degradation, as well as optimizing the chemical environment at the substrate-microbe interface [89,[112][113][114][115][116]. In several cellulosome-producing bacteria, including C. thermocellum, the cellulosome is anchored to the surface of cells, resulting in one of the most efficient systems for bacterial cellulose hydrolysis [4,116].…”
Section: In Vivo Surface-anchoring Of Recombinant Cellulosomesmentioning
confidence: 99%